Engaging in mobile phone-based activities for learning vocabulary: An investigation in Japan and Taiwan. (20th January 2015) - Unknown
Abstract : Studies investigating the use of mobile technologies when other options are available are still relatively rare in the literature, with the majority of studies requiring that learners use a particular technology, either using their own devices or devices provided by the institution. One exception to this was a study by Stockwell (2010) that examined how learners in Japan perceived the use of mobile phones for language learning and how willing they were to engage in the activities. This study, however, was conducted prior to the spread of smart phones and it focused exclusively on learners in Japan. Thus, the purpose of the current study was conducted in two parts. The first part was run in essentially the same environment as the original study but where the majority of learners owned smart phones. The second part used the same system but was conducted with learners studying English at a university in Taiwan. Data were collected through server logs, post-treatment questionnaires and semi-structured interviews. The results are discussed in terms of the ways in which learners engaged in the activities on their mobile phones, and the effect of the mobile platform on the time taken to complete the activities over the course of the semester. These results were correlated with those from the original 2010 study to identify the potential effect of the smart phone.